TATO Model : A concept for a better assessment at the Competency Certification Institute - Aliyyah, Rusi Rusmiati; Mulyadi, Didi; Mohd Yusof, Rosylin Binti (Universitas Negeri Semarang, 2023)
The educational institution, both formal and informal, is aimed at highly competent graduates. One of the tools for quality improvement is the creation of an assessment model. This research identifies and analyses the model of assessment carried out by the certification bodies, namely the TATO model. The research used bibliography and qualitative research models in which qualitative data was obtained through group discussion forums within the competence certification body and the course and training directorate, while the documents were obtained and analysed under the rubric of each competence certification body. The result shows that the TATO model could provide more comprehensive skills for participants in the field of skills. The model could also provide a better understanding for the assessors of the score participants during the test. The result of the model-based competency test would be openness, fairness, measurable and objective. This result could be a great assessment model to maintain the quality of the company and would give confidence to businesses and industries that use staff graduated from training and training institutions. The model would enhance the use of non-formal graduates to meet their human resources needs for technical positions